2019
DOI: 10.1111/jocn.15070
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nursing students’ use of the Fundamentals of Care framework in case‐based work

Abstract: Aims and objectives:To explore how nursing students perceive and use the conceptual Fundamentals of Care framework in case-based work in nursing education and furthermore to describe influencing factors on perceptions and use of the framework. Background:The Fundamentals of Care framework has been integrated in core courses in two Schools of Nursing in Region North Denmark in response to studies reporting that nursing students and newly graduated nurses lack the knowledge, skills and competencies to meet the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…However, Huisman‐de Waal et al (2018) suggested that students, regardless of the stage in their education, acquired greater learning about fundamental care from their clinical placements as opposed to their theory classes. Other research has supported this finding, as Voldbjerg et al (2019) found students were able to integrate the fundamentals of care framework into their clinical settings more effectively by making real‐life connections to their education in clinical contexts. This suggests that educators may need support to learn about how to best address these challenges and take advantage of student engagement across multiple care settings.…”
Section: Discussionmentioning
confidence: 80%
“…However, Huisman‐de Waal et al (2018) suggested that students, regardless of the stage in their education, acquired greater learning about fundamental care from their clinical placements as opposed to their theory classes. Other research has supported this finding, as Voldbjerg et al (2019) found students were able to integrate the fundamentals of care framework into their clinical settings more effectively by making real‐life connections to their education in clinical contexts. This suggests that educators may need support to learn about how to best address these challenges and take advantage of student engagement across multiple care settings.…”
Section: Discussionmentioning
confidence: 80%
“…Supplementary to Mudd et al ( 2020 ), the findings of this study suggests that the framework has the potential to modify the gap between education in school and clinical placements. However, the potential of the FoC framework to accommodate the challenges of a gap requires an early and explicit integration of the FoC framework in nursing education at school and in clinical placements (Feo et al, 2018 ; Voldbjerg et al, 2020 ). Furthermore, it is essential that faculty members and clinical supervisors are well‐informed on FoC and engaged in how to integrate the FoC framework in the supervision of nursing students (Voldbjerg et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of the FoC framework to accommodate the challenges of a gap requires an early and explicit integration of the FoC framework in nursing education at school and in clinical placements (Feo et al, 2018 ; Voldbjerg et al, 2020 ). Furthermore, it is essential that faculty members and clinical supervisors are well‐informed on FoC and engaged in how to integrate the FoC framework in the supervision of nursing students (Voldbjerg et al, 2020 ). According to the supervisors, the link between school and clinical placement created a sense of familiarity to the students which enhanced a positive learning environment and provided a safe starting point for students to learn about nursing in an unknown setting and specialty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…University‐based) nursing education and clinical practice (e.g. acute care, long‐term care; Jangland et al, 2016, 2017; Rey et al, 2020; Voldbjerg et al, 2018, 2020). Although the Framework requires further testing in a wider range of healthcare settings and geographical contexts, it represents the most comprehensive conceptualisation of fundamental care currently available, where care delivery is understood as holistic and integrated rather than simply a series of disaggregated tasks (Feo, Kitson, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%